2018
DOI: 10.1039/c8dt03262a
|View full text |Cite
|
Sign up to set email alerts
|

The coordination chemistry of lanthanide and actinide metal ions with hydroxypyridinone-based decorporation agents: orbital and density based analyses

Abstract: Ligand-to-metal charge transfer, orbital-mixing, chelatoaromatic effect and topological constraints control the binding of lanthanide and actinide ions to hydroxypyridinone-based decorporation agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 59 publications
4
41
0
Order By: Relevance
“…For Th 4+ and Pu 4+ , ten and eight water molecules were considered, respectively, in the primary coordination sphere. We have recently justified the aforementioned choice of hydrated models in our published article . Although some ambiguity remains on the most‐probable hydration number of U 4+ and Np 4+ , ab initio molecular dynamics simulation studies on U 4+ hydration by Atta‐Fynn et al suggested that nine water molecules can be accommodated in the first coordination sphere .…”
Section: Computational Detailsmentioning
confidence: 94%
See 4 more Smart Citations
“…For Th 4+ and Pu 4+ , ten and eight water molecules were considered, respectively, in the primary coordination sphere. We have recently justified the aforementioned choice of hydrated models in our published article . Although some ambiguity remains on the most‐probable hydration number of U 4+ and Np 4+ , ab initio molecular dynamics simulation studies on U 4+ hydration by Atta‐Fynn et al suggested that nine water molecules can be accommodated in the first coordination sphere .…”
Section: Computational Detailsmentioning
confidence: 94%
“…The initial structural coordinates of the [PuL 2 ] complex for geometry optimization were taken from the reported crystal structure by Gorden et al Recently, we investigated the binding of Ln 3+ , An 3+ , and An 4+ metal ions with the L1 ligand computationally . The applied computational methodologies in these works were noted to produce an excellent correlation with the available experimental information.…”
Section: Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations